Incidência de neutropenia induzida por quimioterapia no tratamento do câncer colorretal - Rafael Fernando Mendes Barbosa; Bruna Francielle Toneti; Juliana Maria de Paula Avelar; Amanda Fonseca Baviera; Liyoko Okino; Namie Okino Sawada (Universidade Federal do Ceará, 2019)
Objective to analyze the incidence of neutropenia in patients with colorectal cancer, undergoing chemotherapy treatment.Methods integrative review performed in the following databases: National Library of Medicine, National Institutes of Health, Cumulative Index to Nursing and Allied Health Literature, Latin American literature and Caribbean Center in Health Sciences, and SciVerse Scopus.Results 499 articles were identified, of which 15 met the criteria for inclusion, published between 2006 and 2016 and analyzed in their entirety. Neutropenia was the most reported hematologic toxicity in 12 (80.0%) studies, and the second most common in three (20.0%), in varying degrees, being responsible for reducing and/or delaying of doses in six (40.0%) studies.Conclusion the studies included in this review showed that neutropenia in patients with colorectal cancer in chemotherapy treatment have low incidences in different degrees, despite the significantly high rates of neutropenia associations, as the most common adverse event in the various analyzed regimes.